Naming God in early Judaism: Aramaic, Hebrew, and Greek - Meyer, Anthony R. (Studies in cultural contexts of the Bible, 2022)
Intro -- Table of Contents -- Abstract -- Acknowledgments -- Part I Introduction -- Chapter 1 The Name of God -- 1.1 Sources and Method -- 1.2 Names and Epithets -- Chapter 2 YHWH Adrift and the Quest of Modern Scholars -- 2.1 Summary of Modern Scholarship -- Part II Naming God in Aramaic -- Chapter 3 From Elephantine to the British Museum Drachm -- 3.1 The Elephantine Papyri and Ostraca -- 3.2 Ostraca -- 3.3 Mibtahiah Archive -- 3.4 Anani Archive -- 3.5 Jedaniah Archive -- 3.6 Papyrus Amherst 63 -- 3.7 Idumean 'House of YHW' Ostracon -- 3.8 British Museum Drachm -- 3.9 Conclusion -- Chapter 4 Mount Gerizim, Ezra, and Daniel -- 4.1 Mount Gerizim Inscriptions -- 4.2 Ezra -- 4.3 Daniel -- Chapter 5 Aramaic Dead Sea Scrolls -- 5.1 Enoch -- 5.2 The Book of Giants -- 5.3 Birth of Noah (or: Elect of God) -- 5.4 Genesis Apocryphon -- 5.5 Tobit -- 5.6 The Aramaic Levi Document -- 5.7 Testament of Qahat -- 5.8 Visions of Amram -- 5.9 Words of Michael -- 5.10 4QTestament of Judah? -- 5.11 Son of God Text (or: Aramaic Apocalypse) -- 5.12 Four Kingdoms and other Visionary Texts -- 5.13 Prayer of Nabonidus -- 5.14 Pseudo-Daniel Texts -- 5.15 Jews at the Persian Court -- 5.16 New Jerusalem -- 5.17 Other Aramaic Texts -- 5.18 Aramaic Translations: Job, Leviticus, and Isaiah -- 5.19 Summary of Divine Titles and Epithets in Aramaic -- Part III Naming God in Hebrew -- Chapter 6 Qumran "Biblical" Scrolls -- 6.1 The Divine Name and the Tripartite Division of Hebrew Scrolls -- 6.2 The Qumran Biblical Scrolls -- 6.3 Text-Critical Observations on Divine Name Transmission -- 6.4 Divine Name Variant Patterns -- 6.5 Scribal Changes and Corrections to the Divine Name -- 6.6 Paleo-Hebrew Script in Qumran Biblical Scrolls -- Chapter 7 Qumran Yahad Scrolls -- 7.1 Use and Avoidance of the Divine Name -- 7.2 The title אל replaces the Tetragrammaton.